(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: The article makes an attempt to define health state and probable illnesses of the last hetman of Ukraine Kyrylo Rozumovskyi in the last years of his life. Methods: The study is based on using and analyzing of the memoirs and biography books, containing records and detailed description of health state of K. Rozumovskyi, and documentary archive materials with the samples of his handwriting. To analyze the handwriting of K. Rozumovskyi, the special graphological test developed by Polish physicians of National Health Institute in cooperation with psychologists and graphologists was used. Results: According to the authors’ conclusions, K. Rozumovskyi suffered from diabetes mellitus, gout, and ischemic heart disease. He was vulnerable to common cold also. It is assumed that these diseases contributed to the myocardial infarction which caused his death in 1803. Conclusion: Considering the lack of the system of professional medicine in XVII, XVIII, early XIX century, using graphological method for determining the health of well-known people of these times, is effective. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.90-93